Engaging the private sector to improve antimicrobial use in the community - Luh Putu Lila Wulandari; Virginia Wiseman (Universitas Udayana, 2018)
The private sector has been an overlooked but major source of AMR in many LMICs, including Indonesia. Private drug sellers such as community pharmacies and drug stores therefore have a major part to play in educating patients, rationalising antibiotic use, and stopping antibiotic sales without a prescription. Drafting new laws and regulations to govern the private sector is, however, unlikely to provide a comprehensive solution to the problem of AMR. AMR research must be broadened to include the evaluation of multi-faceted interventions that better reflect the complex incentives and preferences of private drug sellers and their clients. This evidence is urgently needed as countries like Indonesia finalise their National Action Plans and begin rolling out AMR related activities.